2005
DOI: 10.1074/jbc.m502402200
|View full text |Cite
|
Sign up to set email alerts
|

The N-Acetyl-D-glucosaminylphosphatidylinositol De-N-acetylase of Glycosylphosphatidylinositol Biosynthesis Is a Zinc Metalloenzyme

Abstract: The de-N-acetylation of N-acetyl-D-glucosaminylphosphatidylinositol (GlcNAc-PI) is the second step of mammalian and trypanosomal glycosylphosphatidylinositol biosynthesis. Glycosylphosphatidylinositol biosynthesis is essential for Trypanosoma brucei, the causative agent of African sleeping sickness, and GlcNAc-PI de-N-acetylase has previously been validated as a drug target. Inhibition of the trypanosome cell-free system and recombinant rat GlcNAc-PI de-N-acetylase by divalent metal cation chelators demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 38 publications
(44 reference statements)
1
57
1
Order By: Relevance
“…More recent reports on the active domain from rat PIG-L have suggested that it is an extremely 1,10-PO-sensitive metalloenzyme that does not recover activity upon long incubation with the chelator (18). However, the E. histolytica PIG-L appears to be different from rat PIG-L because a similar sensitivity to either EDTA or 1,10-PO was not observed in our assays.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…More recent reports on the active domain from rat PIG-L have suggested that it is an extremely 1,10-PO-sensitive metalloenzyme that does not recover activity upon long incubation with the chelator (18). However, the E. histolytica PIG-L appears to be different from rat PIG-L because a similar sensitivity to either EDTA or 1,10-PO was not observed in our assays.…”
Section: Discussioncontrasting
confidence: 41%
“…Divalent Cations Stimulate De-N-acetylation-Previous reports have suggested that the catalytic domain of rat PIG-L is a metalloprotein that lost activity irreversibly when treated with metal chelators for long periods of time (8,18). Hence, we tested whether MBPEh⌬TMPIG-L was also a metal-dependent de-N-acetylase.…”
Section: Tm Deletion Results In a Functionally Folded Protein Capable Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…This was somewhat surprising, because low-GC bacteria, including Staphylococcus, do not have MSH metabolism. However, MSH S-conjugate amidase and the other M. tuberculosis paralogs, MshB and the uncharacterized protein Rv0323c, belong to a large family of zinc metalloproteinases with homologs in eukaryotes (143,154), low-GC gram-positive bacteria, such as the staphylococci and the bacilli (25,139), and DeinococcusThermus (42). Since the bromotyrosine natural products (100) and analogs contain the zinc-binding hydroxamate moiety, it is not difficult to envision inhibition of this large family of proteins by inhibitors such as EXEG1706 (Fig.…”
Section: Msh Drug Targets In Mycobacterium Tuberculosismentioning
confidence: 99%
“…Building on this model, Ferguson and co-workers used semi-quantitative complementation assays in conjunction with homology modeling to study the metal-binding and catalytic residues of rat PIG-L (12). From this data, they proposed a role for His-49 and Asp-52 of the AHPDD motif, along with the C-terminal His-157 of a HSNH motif, in metal binding.…”
Section: Discussionmentioning
confidence: 99%